Predictors of favorable outcome after endovascular thrombectomy for acute ischemic stroke due to large vessel occlusion in young patients. (December 2022) - Szmygin, Maciej; Sojka, Michał; Tarkowski, Piotr; Pyra, Krzysztof; Luchowski, Piotr; Wojczal, Joanna; Ficek, Remigiusz; Drelich-Zbroja, Anna; Jargiełło, Tomasz
Background: Mechanical thrombectomy (MT) became a standard of care for patients with acute ischemic stroke (AIS) with its efficacy demonstrated by meta-analysis and randomized studies. Although ischemic stroke is associated more with older patients, it may also have devastating neurological effects on young patients. Purpose: To present our experience with stroke patients aged <50 years treated with endovascular means and to evaluate clinical and procedural factors associated with outcome and mortality. Material and Methods: This study was conducted on 34 young stroke patients treated with MT. Clinical features including baseline results, radiological imaging, procedural details, and outcome results were documented and evaluated. Recanalization was assessed according to the TICI score. The clinical condition was evaluated after three months using mRS. Mortality rate was calculated. Results: The rate of successful recanalization (TICI ≥2c) was 79% (27/34). Symptomatic intracranial hemorrhage (sICH) was observed in 5 (15%) patients. After 90 days, the mortality rate was 12%. Favorable clinical outcome (mRs 0–2) was regained in 65% of the patients whereas satisfactory clinical outcome was seen in 85%. Poor clinical outcome (mRs >2) was observed in 9 (23.7%) patients. Conclusion: In conclusion, the results of this study demonstrate that MT for AIS in young patients is feasible and provides an excellent rate of arterial recanalization and high rate of favorable outcomes. Statistical analysis showed that shorter time from onset to arrival and reperfusion, successful recanalization and absence of hemorrhagic transformation are the predictors of favorable clinical outcome and overall survival rate.